Microwave-Assisted Synthesis of Tetrahydrocarbazole Linked 1, 2-Diazoles in Aqueous-Brønsted Acid Catalytic System. (29th October 2017) - Sadiq, Zubi; Hussain, Erum Akbar; Naz, Narjis; Ghani, Ambreen; Yasmeen, Kausar; Iqbal, Fizzah
Abstract : A new series of tetrahydrocarbazole coupled 1, 2-diazoles 4/5/6(a–o) in moderate to excellent yield was synthesized successfully via multicomponent reaction approach by adopting Michael type-addition of hydrazines on in situ generated α, β -unsaturated ketones via aldol type strategy under synthetic microwave radiations and conventional heating. Structural confirmations of all the prepared compounds were achieved by spectroscopic techniques. The best results were achieved when equal amounts of water-acetic acid were used in microwave conditions in 4 minutes.